Heteropoda species from limestone caves in Laos (Araneae: Sparassidae: Heteropodinae) - Bayer, Steffen; Jäger, Peter (Zootaxa, 2009)
Two new Heteropoda species from Laos are described, Heteropoda steineri sp. nov. (male, female) from the Xe Bangfai cave system in Khammouan Province, and Heteropoda aemulans sp. nov. (male, female) from caves close to Vang Vieng in Vientiane Province. Two further species, Heteropoda maxima Jäger, 2001 from Khammouan Province and Heteropoda simplex Jäger and Ono, 2000 from northern Laos and Japan, are recorded. Heteropoda simplex is recorded for the first time from Laos, the female is described for the first time. Main morphological differences between species are recognised from copulatory organs and colouration. Intraspecific variation is illustrated for all species.